The direction of trade and its implications for labour in South Africa - Cameron, Iona R (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2005)
This aim of this thesis is to analyse the demand for labour from trade with a selection of South Africa's trading partners. It is expected that labour demand will be greater in trade with developed blocs. Trade between developing blocs, however, is thought to be more skilled labour intensive and such trade should have greater linkages. This ought to feed through into greater labour demand so that South-South trade may be more 'labour creating' than expected. As it is more skill intensive, it may also be more dynamic, which has implications for future growth and development. Factor content methodology is used to assess labour demand. Calculations consider linkages to other sectors (which will increase labour demand) and the use of scarce resources (which has an opportunity cost to labour). The findings support the claim that trade with developing blocs is more professional labour intensive. Evidence that it may be more dynamic and have greater linkages to labour is borne out in exports to SADC. Greater labour demand through linkages, however, is not evident in net trade to SADC. Neither are they of significance in trade with any of the other developing blocs so labour effects due to linkages appear to be negligible. The advantages of South-South trade may rather lie in the dynamic benefits that trade in higher technology goods provides. When scarce resources such as capital and professional labour are taken into account, it is found that labour demand is negative in net trade to all blocs. However, even without the problem of scarce resources, most blocs have a negative demand for labour in net trade. The indication is that with the present trade patterns, South Africa cannot expect trade to increase labour demand. Policy which could improve this situation would be to increase labour force skills, improve the flexibility of the labour market and develop sectors which are both more advanced as well as labour intensive. Despite the negative impact of trade on labour in general, it is found that trade does differ by direction and that for each labour type there are certain blocs where labour demand is positive. This is also the case in net trade for particular sectors. Such information could be used as part of a targeted trade policy to assist in the marketing of particular sectors in trade and also for increasing labour demand for certain labour groups.
Keywords: Labor demand -- South Africa; Labor market -- South Africa; Industrial relations -- South Africa; Foreign trade and employment -- South Africa; International economic relations; Free trade -- South Africa; South Africa -- Commercial policy